MOTIVASI MAHASISWA MENGAKSES SITUS PORNOGRAFI ONLINE STUDI KASUS MAHASISWA SEKITARAN PANAM PEKANBARU - Maulana Rasyidin; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The purpose of this study was to determine the motivation of students accessing pornography, the impact after watching pornography and sexual acts of students after accessing pornography. The research method used in this research is descriptive qualitative, where the informants taken came from students of Riau University with different departments and faculties. To determine the informant researchers used purpose sampling techniques and data collection techniques by observation and interview. Student's motivation to access online pornography sites on smartphones because of the encouragement of curiosity and to get the desired sexual fantasies. Smartphones and the internet cannot be separated, because the internet is a supporting application that is needed by the community. But in this modern age the internet is widely used by the public, as well as the spread of pornography in the form of electronic information. Indonesia is a country that cannot be separated from the problem of pornography, Indonesia is ranked second out of the 10 largest countries in the world as accessors of cyberporn. This greatly motivates students to access pornographic sites. From the results of observations and interviews, it can be seen that the motivation of Riau University students to access pornography sites is that six out of seven informants are curious and imitate what they see. Keywords : Motivation, Pornography, Smartphones